KAJIAN IMPLEMENTASI TRI DHARMA PERGURUAN TINGGI SEBAGAI FENOMENA PENDIDIKAN TINGGI DI INDONESIA - Yuliawati, Sri (MAJALAH ILMIAH WIDYA, 2012)
Tri Dharma Perguruan Tinggi has three activities namely: (1) Educational field aims to intellectual life of the nation, and culturaltransmission, (2) Research which is to carry out of the new discoveries in science and culture, and (3) the field of dedication tocommunity which is to carry out the service to the community in speeding the process of improving the welfare and progress of thesociety. The objective of this paper is to discuss the implementation the Tri Dharma perguruan Tinggi in order to give input andthought to the government, educational institutions and other stakeholders, as their consideration to take strategic policies for betterand perfect development. The method used is survey through observation at several private universities in Jakarta, interviews to somecollege personnel equipped with several related references. The data was collected from December 2010 until February 2011. It canbe concluded that several obstacles factors in the implementation of the Tri Dharma College are: (1) the lack of higher school facilitiesand infrastructures; (2) the performance of educator and educational which has not been optimum (3) the improper higher schoolmanagement system; and (4) the quality of higher school graduate has not been optimum.